Self-Nanoemulsifying Isotretinoin Topical Formulation: Development, Optimization and Characterization, in vitro Permeation Study by Using Response Surface Methodology - Ghangas, Sandeep; Ashok, Praveen Kumar; Hooda, Tanuj (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim/Background: The objective of this research was to develop a nano-emulsified formulation by using a central composite design for topical drug delivery. Materials and Methods: Isotretinoin-loaded nano-emulsified drug delivery system was prepared for topical application. Surface response methodology was used for the Design Of Experiment (DOE) using Central Composite Design (CCD). A combination of roseship and soyabean oil was used as the oil phase for the development of the formulation. Kolliphor® EL and Transcutol® P were used as surfactant and co-surfactant, respectively. The impact of independent parameters, percentage of oil phase (X1), and surfactant to co-surfactant ratio (X2) were checked at three levels of dependent variablesviz particle size and drug permeation. Results: p-value in ANOVA tables indicate a significant impact of both independent parameters on dependent parameters. R-sq and R-sq(adj) in both regressions is above 99%, confirming the model's suitability. The final formulation contains 22.07% of the oil phase. The ratio of surfactant and co-surfactant is 40:60. It helped to achieve a minimum particle size of ~280 nm and a maximum percentage permeation of ~ 70%. The optimized formulation was characterized for particle size, zeta potential, refractive index, polydispersity index, thermodynamic stability, and percentage drug permeation. Conclusion: The optimum percentage of the oil phase and surfactant to co-surfactant ratio improved the drug permeation when compared with the marketed formulation.
Keywords: Isotretinoin; Photostability; Solubility; in vitro drug Permeation